THE ANALYSIS OF FIGURATIVE EXPRESSIONS IN ADVERTISEMENTS APPEARING IN THE 2016 ISSUES OF GLAMOUR MAGAZINE - ., I Gede Widiana Pradana; ., Prof. Dr.I Ketut Seken, M.A.; ., Dr. Dewa Putu Ramendra, S.Pd., M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Kegiatan pemasaran melalui iklan semakin populer di masyarakat. Kegiatan beriklan menggunakan bahasa kiasan yang sangat menarik untuk mempengaruhi para pembaca. Bahasa pada iklan tidak dapat dimaknai secara harfiah karena mengandung makna makna kiasan di dalamnya. berdasarkan hal tersebut kajian studi tentang iklan ini dilaksanakan. penelitian ini berjutuan untuk mengidentifikasi jenis ekspresi kiasan yang digunakan, menganalisa keberhasilan fungsi dari ekspresi kiasan yang digunakan, dan menginterpretasi makna sebenarnya yang terkadung pada ekpresi kiasan dalam iklan. sumber data pada penelitian ini adalah teks iklan pada majalan Glamour yang di terbitkan pada bulan Agustus hingga Desember tahun 2016. penelitian dilaksanakan dengan metode deskripsi kualitatif. Data diperoleh dari teks iklan yang ditulis dengan ukuran besar. Data dianalisis dengan metode dokumen analisis. berdasarkan penelitian ditemukan sepuluh jenis ekspresi kiasan yang digunakan pada iklan diantaranya: hyperbole (19), personification (13), alliteration (10), metonymy (5), parallelism (4), metaphor (3), simile (2), paradox (2), onomatopoeia (2) dan apostrophe (2). Terdapat empat fungsi dari ekspresi kiasan pada iklan diantaranya: to give imaginative pleasure (31), to add emotional intesity (18), to bring additional imagery (10) dan for saying much in bref compass (6). Makna dari ekspresi kiasan mengandung makna yang tidak dapat diartikan secara harfiah, konotasi, dan makna sesuai konteks. makna pada ekpresi kiasan haruslah dimaknai berdasrkan pada elemen-element disekitarnya pada iklan.Kata Kunci : ekspresi kiasan, fungsi, makna, iklan Marketing through advertisement is popular nowadays. It uses persuasive language which is attractive for influencing readers. The language in advertisement cannot be taken literally, it applies figurative meaning inside the advertisement. Considering to the thought above, the analysis study on advertisement was conducted. This research was aimed at identifying the types of figurative expression used in advertisement, analyzing successfulness of function of figurative expression and interpreting the meaning intended by figurative expression. The data source of this research were the text of advertisements from Glamour Magazine published in August 2016 to December 2016. This study employed descriptive qualitative method. The data were taken from the larger typed text on the advertisements. The data were analyzed using a document analysis method. The research findings showed there were ten types of figurative expressions that appeared in advertisement: hyperbole (19 times), personification (13), alliteration (10), metonymy (5), parallelism (4), metaphor (3), simile (2), paradox (2), onomatopoeia (2) and apostrophe (2). There were four functions served by figurative expression they were to give imaginative pleasure (31 times), to add emotional intensity (18), to bring additional imagery (10) and for saying much in brief compass (6). The meaning of the figurative expression contained non literal meaning, connotative and contextual meaning. It could not be taken literally and should be interpreted by relating to the surrounding elements of advertisement.keyword : figurative expression, meaning, advertisement